Pulsatile mhd flow of two immiscible nanofluids through a porous channel with slip effects - Medisetty, Padma Devi; Suripeddi, Srinivas; Badeti, Satyanarayana; Kuppalapalle, Vajravelu (Zielona Góra: Uniwersytet Zielonogórski)
The present study investigates the effects of shape factor nanoparticles on an oscillatory MHD flow of a nanofluid in two immiscible liquids in a horizontal porous channel with velocity and thermal slip on the walls. Thermal radiation, Joule heating, viscous and Darcy dissipations have been accounted for in the model. We have considered Al2O3 and Cu as nanoparticles, in the lower region (Region-I) and upper region (Region-II): respectively, with water as a base fluid.
Keywords: velocity and thermal slips; Darcy dissipation; Joule heating; volume fraction; shape factor